Analisis Keterlibatan Orang Tua Terhadap Keberhasilan Kualitas Pembelajaran Bagi Peserta Didik di Sekolah MAN 1 Madina - Nurul Mutiah; Novebri Novebri (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Education plays a vital role in shaping high-quality human resources, and parental involvement is crucial for achieving optimal outcomes. This research focuses on MAN 1 Madina, which aims to produce a generation that excels and possesses Islamic character. Parental involvement in this school varies, with some parents actively helping their children learn, while others face challenges. The role of parents in the learning process and the impact of their involvement on the quality of their children’s education is the objective of this study. Using students, parents, and teachers as research subjects, a qualitative descriptive approach was employed. The results indicate that active parental involvement influences students’ motivation and academic achievement. The study also identifies supporting and inhibiting factors of parental involvement, which can be utilized by the school to strengthen collaboration between parents and the school.